Regional Interference in Afghanistan and its Implications for Regional Peace and Security - Usman, Tehseena; Ghufran, Nasreen; Majeed, Minhas (The Journal of Humanities & Social Sciences, 2023)
Owing to Afghanistan’s geostrategic location, diverse ethnic composition, decentralized governance and socio-political structure, outside interference has been a historical phenomenon. However, 1978 can be treated as a watershed which changed the entire dynamics and context of foreign interference in the country. The Soviet invasion of Afghanistan triggered by global power politics and developments subsequent to Soviet forces withdrawal in 1989, accentuated prospects of competition among regional players. The extreme rivalry proved to be self-defeating for regional countries as their policies were not well grounded. The covert manipulation of Afghan policies by regional countries together with Afghans own internal divisions and divergent interests have had serious repercussions for Afghanistan’s stability and that of the region as a whole. Most importantly none of the regional players have managed to achieve their self-defined objectives in Afghanistan. The dire instability and insecurity has deprived all the regional countries of economic dividends and development. The paper suggests that the self-interests of each of the regional countries would be best served through collaboration and problem-solving approach. This would demand more nuanced focus on shared interests, cooperation and a broad common vision that would promote an atmosphere of mutual trust and confidence. This article attempts to highlight the regional interference in Afghanistan and its implications for regional security. Moreover, it contends that common destiny of the region is interwoven through history and a collective prosperous future.